Kegiatan Peningkatan Pengetahuan Pembukuan dan Laporan Keuangan pada Usaha Kerupuk Rambak Di Desa Jumeneng Kecamatan Bangsal Kabupaten Mojokerto - Armin, Rini; Ambarsari, Retno (Fakultas Ekonomi Universitas Islam Majapahit, 2022)
This activity to increase knowledge of bookkeeping and financial reports in the Rambak Cracker Business in Jumeneng Village, Bangsal District, Mojokerto Regency, was carried out in more than 6 months from August 1, 2021 to December 31, 2022. The objectives of this include: (1) Efforts to increase partner understanding about the importance of the benefits of bookkeeping and financial reports in managing a business; (2) Technical training as well as assisting partners in making books and financial reports. The implementation methods in this activity include: interviews and observations, training on bookkeeping and assistance during the implementation of activities. Thus, it is hoped that the problems faced by partners can be solved, especially those related to the management of the cracker rambak business by providing adequate financial bookkeeping so that they can perform well and sustainably.